Pengembangan Packaging Produk Keripik Singkong untuk Menambah Nilai Jual Produk Menuju Ketahanan Ekonomi di Desa Pandan Sari - Sampena, Iwan Doa; Adam, Firsa; Gunawan, Rizki; Ramadhani, Renggalis; Agustina, Agustina; Arba’iah, Arba’iah; Afrina, Siti; Ayuni, Riska Elpa; Lusanti, Nadia Sri (Medan Resource Center, 2024)
Pandan Sari Village itself is one of the villages in Simpang Kanan District, Singkil Regency, Aceh Province. The local potential in Pandan Sari Village is MSME actors and is supported by the results of natural resources (SDA). The majority of the population of Pandan Sari village, the source of income of the general community, namely as MSME actors, one of which is Mr. Sugino's Cassava Chips. Marketing and product packaging are still classified as very simple, only using clear paper plastic without using product identity status, namely without labels and seen from marketing activities that are not yet effective. Community service through programs in assisting and providing training to the community to develop the products of MSME players in Pandan Sari Village so as to create community economic resilience through local potential. With the survey and observations that have been made, the service team has made efforts to help the welfare of the community, one of which is by helping the community of MSME players in packaging innovation, namely product labels and product banners in the hope of increasing the selling value of cassava chips products in Pandan Sari Village. There are several stages carried out starting from socialization and interviews to education to the community for the application of product innovation so that Cassava Chips products are capable and feasible to develop in order to create economic and social resilience of the community.